HVPE growth of thick Al0.45Ga0.55N layers on trench patterned sapphire substrates. Issue 3 (21st December 2012) - Hagedorn, Sylvia; Richter, Eberhard; Zeimer, Ute; Weyers, Markus; Toropov, Alexey; Ivanov, Sergey
Abstract In this work results on the influence of the total pressure, V/III ratio and substrate miscut direction on the growth of Al0.45Ga0.55N on trench patterned sapphire by hydride vapour phase epitaxy are presented. It was found that for trenches running along the [11‐20]sapphire direction a substrate miscut towards m‐plane is favourable to obtain a coalesced c‐plane oriented AlGaN layer. With an optimized total pressure and V/III ratio coalesced flat c‐oriented AlGaN layers of up to 40 µm thickness were grown. The layers show transparency for wavelengths above 280 nm. An abrupt change in the luminescence spectra from band edge dominated to yellow luminescence dominated emission was found at the change over from uncoalesced to coalesced regions. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)